The effect of bempedoic acid an ATP-citrate lyase inhibitor on cardiovascular risk factors in rats with experimentally induced myocardial infarction and hyperlipidemia: Effect of bempedoic acid an ATP-citrate lyase inhibitor - Yaseen, Mahmood Salim; Mohammed Ali, Nidhal (Cellular and Molecular Biology, 2022)
Control of hyperlipidemia is believed to reduce major cardiovascular events such as cardiovascular death, myocardial infarction, nonfatal stroke, hospitalization for unstable angina, and coronary revascularization. The benefits of monotherapy with Bempedoic acid (BA) as a hypolipidemic agent given after induction of myocardial infarction (MI) in reducing the risk of acute MI worth being investigated, therefore this study was designed to investigate the effectiveness of Bempedoic acid on reducing cardiovascular risk factors in rats with induced hyperlipidemia and myocardial infarction compared to Rosuvastatin. Male albino rats (n=40) were divided into five equal groups, each with eight rats, the first group served as a negative control group, the second group (diet-induced hyperlipidemia and Isoprenaline induced myocardial infarction) served as a positive control group, the third group (diet-induced hyperlipidemia and Isoprenaline induced myocardial infarction) received daily oral administration of Rosuvastatin for 12 weeks, the fourth group (diet-induced hyperlipidemia, DIH) received Bempedoic acid for 4 weeks as prophylaxis and then myocardial infarction was induced and Bempedoic acid administration was continued for the remaining 8 weeks, and the fifth group (diet-induced hyperlipidemia and Isoprenaline induced myocardial infarction) received a daily oral administration of Bempedoic acid for 12 weeks as a treatment. After 12 weeks, blood samples were withdrawn by cardiac puncture for measuring and evaluating lipid profiles and other parameters. Bempedoic acid and Rosuvastatin significantly reduce mean serum levels of lipid profiles; Total cholesterol, LDL and triglyceride, increase HDL and reduce cardiac enzyme levels as compared with the positive control group. The findings from this study suggested that Bempedoic acid as monotherapy either as a therapy or as prophylaxis was effective in reducing lipid parameters, LDL, Tch, and TG and cardiac enzymes creatine kinase-MB (CK-MB) and serum level of cardiac troponin-I (cTn-I) compared with the positive control group and was not superior to Rosuvastatin in these parameters but taking BA as prophylaxis could prevent the morbidity with cardiovascular events as it was effective in reducing the above parameters by greater percentages than BA and Rosuvastatin therapy.. Both drugs showed similar profiles in blood pressure and heart rate measurements.